Improving Student Learning Outcomes with Power Point Media Through The Zoom Application on Learning Various Occupational Themes - Kusumawati, Triana (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in learning the various themes of class 4 work. This research was a classroom action research (CAR) which was carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fourth grade students of SD Negeri 02 Tegalsari in the 2020/2021 school year, totaling 14 students. Data collection techniques using tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of power point media can improve student learning outcomes on the subject matter of various jobs in class IV SD Negeri 02 Tegalsari in the 2020/2021 school year as evidenced by the percentage of completeness of learning outcomes in cycle I of 71%, cycle II of 86%, and become 93% in cycle III